Presencia de Ehrlichia mediante frotis sanguíneo en perros del Recinto La Mascota del Cantón Montalvo, Provincia Los Ríos - Huilca Agualongo, Katty Liliana (2024)
The presence of Ehrlichia canis was detected in 1935, by Donatien and Lestoquard of the Pasteur Institute of Algeria, because they visualized organisms similar to rickettsiae in monocytes from febrile and anemic dogs, which is why they were classified as Rickettsia canis. In 1945, Moshovski reclassified them as Ehrlichia canis in honor of Paul Ehrlich, a German bacteriologist, establishing a genus different from Rickettsia. The etiological agent of Ehrlichia is an obligatory intracellular, gram-negative, coccoid-shaped bacteria that requires a mammal as a reservoir and an arthropod as a vector, which affects blood cells. Its main vector is the Brown Tick or Rhipicephalus sanguineus. The objective of this research work was to determine the presence of Ehrlichia through blood smears in the dogs of the La Mascota Campus, which is located in the Montalvo Canton, Los Ríos Province. 50 blood samples from the study dogs were used, according to age, sex and breed, in order to find out how many animals have the disease. A blood sample of 1 to 2 ml is taken directly from the cephalic vein, then it is placed in a tube with EDTA to prevent coagulation, then a blood smear is taken to be stained with Wright's stain. to finally be observed under the microscope. After observing the 50 samples, 22 positive cases for Ehrlichia were obtained, where the mixed breed was more susceptible, as were adult males.